ASSOCIATION OF URANYL WITH THE CELL WALL OF PSEUDOMONAS FLUORESCENS INHIBITS METABOLISM - Bencheikh-Latmani R.; Leckie J.O. (My University, 2003)
Citric acid is found along with uranyl in the subsurface of former nuclear facilities because of its use as a decontamination agent in the nuclear industry. Citrate's metal chelating properties affect the mobility of uranyl in the subsurface and consequently, citrate biodegradation may significantly impact uranyl fate and transport. Under the non-growth conditions considered, low (micromolar) uranyl concentrations inhibit the biodegradation of citrate by Pseudomonas fluorescens, a common subsurface denitrifying bacterium. Additionally, uranyl is found readily associated with the cell envelope of P. fluorescens. The observed inhibition appears to be linked to the binding of uranyl to the cell surface and is reversible by desorbing cell-bound uranyl. This study establishes a link between uranyl association with the cell surface and the observed inhibitory effect of uranyl on cell metabolism.